Applying the FAO surveillance evaluation tool (SET) to assess the fish farming disease surveillance system in Spain - Muniesa, Ana; Ruiz-Zarzuela, Imanol; Lamielle, Gael; Von Dobschuetz, Sophie; Furones, Dolors; Rodgers, Chris; Basurco, Bernardo (Frontiers in Veterinary Science, 2024)
EU Member States should ensure that they implement adequate health surveillance schemes in all aquaculture farming areas, as appropriate for the type of production. This study presents the results of applying the FAO's Surveillance Evaluation Tool (SET) to assess the Spanish disease surveillance system for farmed fish species, which although applied previously in livestock production, is applied here to aquaculture for the first time. Overall, there were important score differences between trout and marine fish (seabass and seabream) surveillance, which were higher for trout in the following areas: Institutional (70.8% versus 50.0%), Laboratory (91.7% versus 47.2%), and Surveillance activities (75.3% versus 61.3%). For other categories, the values were lower and no significant differences were found. However, most surveillance efforts focused only on trout, for which there are EU and WOAH listed (notifiable) diseases. In contrast, for seabream and seabass, for which there are no listed diseases, it was considered that surveillance efforts should, nevertheless, be in place and should focus on the identification of abnormal mortalities and emerging diseases, for which there are as yet no standardized harmonised methodologies.por la que se aprueban las normas reguladoras para la concesión de ayudas a las Agrupaciones de Defensa